2018
DOI: 10.1177/0961000618773140
|View full text |Cite
|
Sign up to set email alerts
|

Administrative and infrastructural factors affecting library and information science educators’ actual use of educational support systems for teaching in Nigerian universities

Abstract: This research assumes that administrative and infrastructural factors may explain the low use of educational support systems (ESS) for teaching by library and information science (LIS) educators in Nigerian universities. The literature has focused on the adoption of different types of educational technologies and their use by teachers and students with little consideration for the LIS educators’ actual use of ESS for teaching and the effect of institutional support on the use of these systems. Thus, the study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Another inhibitor according to literature is funding. It was found that the overall educational system in Nigeria is underfunded and that available funds are used by tertiary institutions to solve more urgent and important survival needs [7,9,22,36]. The development and subsequent operation of ICT require huge financial investment in, and commitment to, the acquisition of necessary facilities and their utilisation and maintenance, hence, the need for finance can never be over-emphasised.…”
Section: Inadequate Fundingmentioning
confidence: 99%
See 2 more Smart Citations
“…Another inhibitor according to literature is funding. It was found that the overall educational system in Nigeria is underfunded and that available funds are used by tertiary institutions to solve more urgent and important survival needs [7,9,22,36]. The development and subsequent operation of ICT require huge financial investment in, and commitment to, the acquisition of necessary facilities and their utilisation and maintenance, hence, the need for finance can never be over-emphasised.…”
Section: Inadequate Fundingmentioning
confidence: 99%
“…An inhibiting factor found during this review is inadequate administrative support. These authors revealed that the attitude and support of leaders in and outside Nigerian institutions towards the development and use of ICT related facilities was either slow, poor or nil [6,7,21,28]. According to Eze, Chinedu-Eze, Okike & Bello, abysmal management commitment to interactive knowledge environment is the bane of electronic teaching and learning.…”
Section: Lack or Inadequate Administrative Supportmentioning
confidence: 99%
See 1 more Smart Citation